Basal release of nitric oxide in the mesenteric artery in portal hypertension and cirrhosis: Role of dimethylarginine dimethylaminohydrolase. Issue 5 (25th April 2013) - Serna, Eva; Mauricio, María Dolores; Lluch, Paloma; Segarra, Gloria; Cortina, Belén; Lluch, Salvador; Medina, Pascual
Abstract Background and Aim Increased basal release of nitric oxide (NO) in the splanchnic circulation contributes to elevated plasma levels of NO observed in decompensated cirrhosis. We evaluated in rat mesenteric arteries whether the differences in basal release of NO, revealed by asymmetric dimethylarginine (ADMA)‐ and NG‐nitro‐L‐arginine methyl ester (L‐NAME)‐induced contractions, were associated with changes in messenger RNA (mRNA) expression of endothelial NO synthase (eNOS) and dimethylarginine dimethylaminohydrolases (DDAHs). Methods Rat small mesenteric arteries from 14 Sham‐control, from 14 with partial portal vein ligation (PPVL), and from 14 with bile duct excision (BDE)‐induced cirrhosis were precontracted under isometric conditions with norepinephrine, and additional contractions were induced with ADMA and L‐NAME. mRNA expression of eNOS, DDAH‐1, and DDAH‐2 in mesenteric arteries were evaluated by real‐time polymerase chain reaction. Results ADMA and L‐NAME caused concentration‐ and endothelium‐dependent contractions. pD2 values to L‐NAME were similar in all groups. In contrast, pD2 values to ADMA were similar in PPVL and BDE but were significantly lower than those of the L‐NAME and the Sham groups. Relaxation to acetylcholine was not modified by ADMA or L‐NAME but was abolished by charybdotoxin plus apamin. There was an increased mRNA expression of eNOS, DDAH‐1, and DDAH‐2 in mesenteric arteries from PPVL and BDE compared with the Sham group. Conclusion Basal release of NO is increased in mesenteric arteries of PPVL and BDE rats. The rise in expression of DDAHs indicates a higher degradation of ADMA. This would result in an increased generation of endothelial NO and mesenteric vasodilation.